Analysis of Sharia Business Unit Spin-Off Regulations and Islamic Law - Lubis, Rahmat Husein; Hulwanullah, Hikam (Al Ahkam, 2024)
Regulations regarding the development of Sharia Business Units (UUS) often experience changes, for example in Law Number 21 of 2008 concerning Sharia Banking in Article 68 paragraph 1. This advice aims to provide clear and specific legal references. Then, the latest regulation regarding UUS issued by the OJK. The Sharia Financial Services Authority (OJK) has issued a regulation regarding the spin-off of Sharia Business Units from Conventional Commercial Banks (BUK). This study aims to analyze OJK regulations regarding Sharia Business Units that have undergone spin-offs from the perspective of the legal system according to Lawrence M. Friedman, focusing on structural, substance, and cultural aspects, as well as the perspective of Islamic law regarding sharia compliance and ethical considerations. The method used is qualitative descriptive, with a sociological juridical approach that evaluates regulations based on legal principles and ethical considerations. Data was collected by means of documentation from Indonesian laws related to spin-offs, including Law Number 21 of 2008 concerning Sharia Banking. This regulation has a positive impact on the development of Sharia Business Units during the spin-off by increasing budget transparency, integrity, and operational efficiency leading to sustainable growth and compliance with Islamic principles.